The BIOLOGICAL CRISIS OF CHILEAN EDUCATION. SCHOOLING AND SOCIAL POLICY, 1930-1960 - Rengifo Streeter, Francisca (Revista de Historia Social y de las Mentalidades, 2019)
This article analyzes the Chilean schooling process during the period in which the State sought to institutionalize universal access to primary education. This goal, contained in the compulsory school law of 1920, was challenged by school desertion and lag showing an extensive social base of education, but thin in terms of the level of schooling. To explain this phenomenon, the article distinguishes between the extension of coverage and the expansion of schooling, identifying internal imbalances in the schooling process. It argues that, despite the social demand for education, public policy did not prioritize the school. The results obtained discuss the assumption that links the expansion of public education to a broader social inclusion agenda framed within the welfare state, whose triumphalist emphasis has obscured its excluding dynamics.